Decontamination Efficacy of Neutral and Acidic Electrolyzed Water in Fresh‐Cut Salad Washing. Issue 5 (15th December 2015) - Ignat, Alexandra; Manzocco, Lara; Maifreni, Michela; Nicoli, Maria Cristina
Abstract: The possibility of washing fresh‐cut vegetables with neutral (NEW) and acidic (AEW) electrolyzed water instead of highly chlorinated solution was investigated. The decontamination efficacy was tested in vitro against P seudomonas fluorescens, which is a typical inhabitant of leafy vegetables. The antibacterial efficacy of NEW and AEW was highly dependent on pH solution. NEW and AEW that were adjusted to a pH analogous to that of salad (6.5) completely inactivate P . fluorescens at 30 mg/L free chlorine concentration. The same result was achieved by sodium hypochlorite aqueous solution at a much higher free chlorine concentration (150 mg/L). NEW and AEW at 30 mg/L free chlorine concentration also reduced total mesophilic count, P seudomonas spp. and total coliforms of salad by circa 1 log cycle. Microbial loads of wastewater deriving from salad washing resulted below the detection limit. Practical Applications: Electrolyzed water can be exploited as a sanitizing washing agent in the fresh‐cut industry allowing to replace conventional chlorination of washing water with highly concentrated NaOCl. Thus, it would be possible to guarantee an analogous decontamination efficacy and decrease the overall presence of potentially toxic chlorine compounds in wastewater. This would contribute to meet the global requirement of reducing the water footprint of industrial washing and reduce the use of harmful disinfection solutions.